The Pattern of Hospital Admissions Prior to Care Home Placement in People With Parkinson's Disease: Evidence of a Period of Crisis for Patients and Carers. (October 2019) - Klaptocz, Joanna; Gray, William K.; Marwood, Sophie; Agarwal, Mitali; Ziegler, Joseph; Webb, Zoszka; Prabhakar, Meghna; Hand, Annette; Oates, Lloyd; McDonald, Claire; Walker, Richard W.
Objectives: We hypothesized that the number and length of hospital admissions in people with Parkinson's disease (PD) would increase immediately prior to admission to a care home relative to those who were able to continue living at home or who died.Method: PD patients at Hoehn and Yahr Stages III to V were followed-up over two and a half years with deaths and care home placements recorded. Hospital admissions data were collected over this period.Results: Of 286 patients included in the study, 7.3% entered a care home and 28.3% died. In the final 120 days prior to the study exit point (care home placement, death, or continued living at home), longer hospital stay was significantly associated with care home placement, after adjusting for the competing risk of death.Conclusion: Our data provide evidence that, for many people with PD, a period of crisis is reached immediately prior to care home placement.